Prostate Carcinoma With Overlapping Features of Small Cell and Acinar Adenocarcinoma: A Case Report. (11th September 2019) - Cordeiro-Rudnisky, Fernanda; Sun, Yue; Saade, Rayan
Abstract: Introduction: Prostate neuroendocrine (NE) cells can stimulate prostate adenocarcinoma (PA) cell growth, but occasionally adenocarcinoma cells themselves acquire NE characteristics, a phenomenon known as NE transdifferentiation of prostate adenocarcinoma. During this process, tumor cells acquire small cell-like morphology and become positive for neuroendocrine markers. NE transdifferentiation is associated with decreased androgen receptor (AR) signaling, a mechanism of resistance to AR-targeted treatments. Case: A 74-year-old male with a history of cirrhosis, splenomegaly, and thrombocytopenia presented with hematuria and urinary obstruction. PSA was 0.31 ng/mL. CT scan demonstrated bladder wall thickening. Surgery showed a bladder tumor, clinically diagnosed as urothelial tumor. Pathology revealed a poorly differentiated carcinoma, with small cell-like morphology. The tumor cells had high nuclear to cytoplasmic ratio, focal nuclear molding, and high mitotic rate, like small cell carcinoma. But the nucleoli were intermediate between small cell carcinoma and usual adenocarcinoma of the prostate. Immunostains showed that the tumor cells were positive for NKX3.1 and focally positive for NE markers, including chromogranin, synaptophysin, INSM1, and FOXA2. The tumor cells were negative for PSA and GATA3. The morphology and immunoprofile are consistent with Gleason pattern 5 PA in transdifferentiation to small cell carcinoma. Discussion: The incidence of neuroendocrine phenotype is 1% in primary PA and 25% in metastatic castrate-resistant PA. Typically, NE transdifferentiation occurs in response to androgen deprivation therapy/AR inhibitors. Pretreatment NE transdifferentiation is relatively uncommon. PA depends on androgens for its progression, which is the basis for antiandrogen therapy. Decreased AR expression associated with NE transdifferentiation is a mechanism of resistance to AR-targeted therapy. These tumors are often more aggressive with worse prognosis. Conclusion: Our patient has Gleason pattern 5 PA with NE transdifferentiation invading the bladder, which is a high-grade, aggressive tumor.